Rise & shine, Benedict Stone - Patrick, Phaedra (Park Row Books, 2017)
In the quiet village of Noon Sun, Benedict Stone lives out the stagnant life of an unhappily married jeweler, until the daughter of his estranged brother arrives from America and turns his whole life upside down.